the phenomenon of miniaturization in the Badinani dialect - Tawfiq, Vajeen (Humanities Journal of University of Zakho, 2020)
This research is entitled (the phenomenon of miniaturization in the Badinani dialect) as it is an attempt to talk abouk the aspects of miniaturization in the Badinani dialect following the ideology (descriptive).The most important results of this research is miniaturization used in all levels of morphology, syntax, and Symantec.